Histórias de mulheres “boêmicas” e “turbulentas” nas “casas de brinquedos” do Bairro do Porto em Cuiabá (1860 - 1888) - Rodrigues, Jhucyrllene Campos dos Santos (2020)
This paper seeks to understand the sexual practices of bohemian and 'turbulent' women in the 'toy houses' of the Porto neighborhood of Cuiabá (1860-1888), as well as the organization of this space, the types of work available in this place for both women and men. especially those linked to taverns, bars, bakeries, taverns and leisure, amusements in the 'Toy- drum' and also, in open houses, where women and men, slaves, liners, freed, free, poor, mestizos, black people participated. The aim of thisstudy is also to focus on the female figure, the workers of the urban spaces of the City of Cuiabá, with emphasis on those who performed in the Second Parish of Dom Pedro II, during the nineteenth century, around the 1860s. 1888, today neighborhood of the port. These were women who worked in local businesses and varioussectors of activities and services, and others who worked independently on the streets, but who in their spare time got used to going out with their friendsforsex in toys. , drumming, cane, siriri and in the free houses. It is a research based on several documentary typologies, as for example; Newspapers; Official Gazette-Monthly Supplement; Proceedings of Crimes Offices of the 6th Office Notary and the Courts of Relations of the series Criminal- Drunkenness, turbulence the Public Order; Murder; Homicide Attempts; Light and heavy bodily injury and among other information were found in the State Public Archive-APEMT and the Historical Documentation Center of Mato Grosso NDIHR of the nineteenth period. The study also drew attention in the field of daily social history, lived by women and men where the concepts of daily life, culture, leisure, fun and sexual practices linked to the spaces of the Second Parish of Dom Pedro II are marked. with Edward P. Thompson, Michel de Certau, Gilberto Freire, Mary Del Priore, Sidney Chalhoub, Martha Abreu, Margareth Rago, Delso Renault, Soares Luiz Carlos. The focus of this paper is to reveal how the social practices of toy-drumming parties linked to sexual practice were experienced by the lower categories of the Cuiabana population in the first half of the 19th century.